OPTIMASI PENGGUNAAN INPUT PRODUKSI PADA USAHATANI BAWANG MERAH DI DESA TORONGREJO KOTA BATU - Sri Wulandari; Sri Hindarti; Bambang Siswadi (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2019)
ABSTRACTTorongrejo village is one of the shallot producing areas in Batu City. However, the use of productions input on shallot farming in Torongrejo Village is not optimal because there is no proper reference in its use, this can be seen from the low actual production compared to its potential production. This study aims to determine the effect of input use on shallot production, as well as knowing the optimum level of use of input onion production. This research was conducted in Torongrejo Village, Junrejo Subdistrict, Batu City on November 8-December 8 2018. Primary data was obtained by interviewing 40 sample farmers who were randomly selected. The data analysis method used is the Cobb-Douglas production function. The results showed that land area, drugs, and labor had a significant effect on shallot production. The area of land and labor has not been used optimally, while medicines are not optimal. Therefore it is necessary to develop shallot plants on wider land, increase labor and reduce drug use to optimize the input of shallot production. Keywords: optimization, Cobb-Douglas production function.